Mild Aromatic L-Amino Acid Decarboxylase Deficiency Causing Hypoketotic Hypoglycemia in a 4-year-old Girl - Merve Yoldaş Çelik; Ebru Canda; Havva Yazıcı; Fehime Erdem; Ayşe Yüksel Yanbolu; Ayça Aykut; Asude Durmaz; Ahmet Anık; Sema Kalkan Uçar; Mahmut Çoker (Galenos Yayincilik, 2024)
Aromatic L-amino acid decarboxylase (AADC) deficiency is a disease in which neurological findings are dominant due to deficiencies in neurotransmitter synthesis. Hypoglycemia caused by autonomic dysfunction is one of the symptoms that may be encountered. Here we report a case of mild AADC deficiency presenting with hypoglycemia without any neurological signs. A 4-year-old girl presented with recurrent hypoglycemia. Her growth and development were normal. Plasma insulin and cortisol values were normal in the sample at the time of hypoglycemia. C8: 1-Carnitine elevation was detected in the acylcarnitine profile. A clinical exome panel was performed with the suggestion of a fatty acid oxidation defect. However, a homozygous variant in the DDC gene was detected. Furthermore, cerebrospinal fluid neurotransmitter analysis revealed low 5-hydroxyindolacetic acid and homovanillic acid and high 3-O-methyl-dopa and methyltetrahydrofolate (5 MTHF) consistent with AADC deficiency. Plasma AADC enzyme activity was low. The episodes of hypoglycemia were treated with uncooked cornstarch. This case suggests that AADC deficiency should be considered in some patients with hypoglycemia.